A Survey on Prevalence of Ocular Complications and It's Risk Factors in Diabetic Patients of Diabetic Center of Nader Kazemi Clinic Shiraz- Iran 1998-2010 - SM Kashfi; A Khani Jeihooni (Fasa University of Medical Sciences, 2013)
Background & Objective: With respect to an increase in diabetes prevalence, and the likelihood of ocular complications among them, this study was conducted to investigate the prevalence and risk factors and incidence of the ocular complications in patients of Nader Kazemi, Shiraz Diabetic center from 1998 to 2010.Materials & Methods: In a cross sectional study , subjects were selected based on a systematic random sampling to investigate the incidence of the ocular complications and the influence of factors such as age, sex, types of diabetes, job, education, blood triglyceride (TG) and cholesterol level, Family history of diabetes, history of hypertension, history of participation in educational classes, methods of treatment, duration of diabetes and fasting blood sugar were considered on them.Results: Ocular complications were found among 229 diabetic patients (32.6%). patients having type II diabetic have more ocular complications comparing with patients with type I diabetes (P<0. 005). Factors such as job (P=0. 022), history of participation in educational classes (P<0. 001), education (P<0. 001), family history of diabetes (P<0. 001), blood triglyceride (TG) (P=0. 021), duration of diabetes(P<0. 001),age (P<0. 001), method of treatment(P<0. 001)and fasting blood sugar (P<0. 001) had a significant relationship with the occurrence of ocular complication. However, other risk factors such as hypertension,gender and cholesterol levels were not statistically significant relationship with the occurrence of ocular complication.Conclusion: Given the prevalence of ocular complications, educating diabetics' patients can have a significant influence in reducing the occurrence of ocular complications.